Myanmar immigrant women's perceptions, beliefs, and information-seeking behaviors with nutrition and food practices during pregnancy in Thailand: a qualitative study - Sasitara Nuampa; Pornnapa Tangsuksan; Kwanchit Sasiwongsaroj; Rudee Pungbangkadee; Somsiri Rungamornrat; Nuntiya Doungphummes; Sittiporn Netniyom; Crystal L. Patil (BMC, 2024)
Abstract Background Although nutrition is an essential contributor to the quality of pregnancy outcomes, little is known about the experiences and influences affecting dietary behaviors during pregnancy among migrant women, particularly those from Myanmar, the largest immigrant population in Thailand. To fill this gap, we conducted a descriptive qualitative study to explore Myanmar immigrant women's perceptions, beliefs, and information-seeking behaviors concerning nutrition and food practices during pregnancy. Methods We conducted focus group discussions (FGDs) with fifty Myanmar immigrant pregnant women aged 18-45 years across all trimesters, who were recruited using purposive sampling from a public tertiary hospital. The FGDs were conducted in Thai or Myanmar using semi-structured guides that probed women's pregnancy perceptions and experiences about nutrition and food patterns during pregnancy. The FGDs were audio-recorded, translated, and transcribed. Direct content analysis was used to guide the analysis through an ecological perspective framework. Results The seven FGDs with fifty women revealed four major themes involving perceptions, beliefs, and information-seeking behaviors. The qualitative results consisted of (1) a positive attitude toward better changes under difficult conditions (setting goals for infant health; uncertainty about changes); (2) beliefs about eating patterns and dietary practices during pregnancy (taboos aimed at protecting women's health and ensuring safe childbirth; taboos aimed at guaranteeing infant safety); (3) limited access to appropriate information about nutrition (unclear dietary information from healthcare providers; ease of learning from experiences in informal social networks); and (4) difficult living conditions in a non-native setting (work-related influences on dietary behaviors; lack of comprehensible language to gain food literacy). In addition, the results were highlighted across four levels of ecological perspectives. Conclusions Immigrant pregnant women are a vulnerable population that should be treated with equity to ensure quality of life through optimal nutrition throughout pregnancy. Respectful care requires that healthcare providers develop culturally sensitive nutrition interventions to increase nutrition literacy, accessibility, and pregnancy outcomes.